Odpowiedzi

2010-01-20T22:22:56+01:00
W(x)=-25x^2-20x-4 = -(5x + 2)²
w(x)=x^3-3x^2+3x-1 = (x - 1)³
w(x)=1+6x+12x^2+8x^3 = (2x + 1)³
w(x)=(9x^2-6x+1)-(4x^2+20x+25) = (3x-1)²-(2x+5)²
1 5 1
Najlepsza Odpowiedź!
2010-01-20T22:48:28+01:00
W(x)=-25x^2-20x-4
w(x)=-(25x^2 +20x + 4)
w(x)=-[(5x)^2 + 2*5x*2 + 2^2]
w(x) = -(5x+2)^2
___________________________

w(x)=x^3-3x^2+3x-1
w(x)= x^3 - 3 * x^2 * 1 + 3 * x * 1^2 - 1^3
w(x) = (x-1)^3
_____________________________________

w(x)=1+6x+12x^2+8x^3
w(x)=1^3 + 3*1^2 *2x+3*1*(2x)^2+(2x)^3
w(x)=(1+2x)^3
_____________________________________

w(x)=(9x^2-6x+1)-(4x^2+20x+25)
w(x)=(3x-1)^2 - (2x+5)^2